Bias in literature search and national scientifi c production in health human resources - Mendoza-Arana, Pedro Jesús (2017)
Mr. Editor In the article by Franco Romaní and collaborators, on the scientific production referred to the national agendas of research in Peru 2011-2014 (1), it is concluded that the research area in Human Resources in Health is the least studied area, with only 4 original articles published, that is, 1.8% of the articles identified in the study period.